2020
DOI: 10.1007/s13337-020-00603-0
|View full text |Cite
|
Sign up to set email alerts
|

Inanimate surfaces as potential source of 2019-nCoV spread and their disinfection with biocidal agents

Abstract: The WHO has declared COVID-19 illness a global health concern which is caused by 2019-nCoV, causing severe respiratory tract infections in humans. Transmissibility among individual to individual have been reported through droplets and probably also via contaminated surfaces and hands. Human coronaviruses can persist on inanimate surfaces such as plastic, glass, fibers and metals up to nine days. 2019-nCoV remains infectious in air for 3 h and on inanimate surfaces such as cardboard, copper, plastic and steel u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 12 publications
0
24
0
3
Order By: Relevance
“…In contrast, on copper surfaces the coronavirus can only sustain approximately 4 h ( Suman et al, 2020 ). Interestingly, a rapid SARS-CoV-2 inactivation is possible by using commonly available chemicals and biocides on inanimate surfaces ( Akram, 2020 ; Dev Kumar et al, 2020 ; Gerlach et al, 2020 ). In summary, although the presence of SARS-CoV-2 on inanimate surfaces is possible, washing hands and regular disinfection practices should reduce the possibilities of transmission of the coronavirus by this potential route of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, on copper surfaces the coronavirus can only sustain approximately 4 h ( Suman et al, 2020 ). Interestingly, a rapid SARS-CoV-2 inactivation is possible by using commonly available chemicals and biocides on inanimate surfaces ( Akram, 2020 ; Dev Kumar et al, 2020 ; Gerlach et al, 2020 ). In summary, although the presence of SARS-CoV-2 on inanimate surfaces is possible, washing hands and regular disinfection practices should reduce the possibilities of transmission of the coronavirus by this potential route of infection.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the potential transmission of SARS-CoV-2 from surfaces, the WHO ( WHO, 2020b ) recommends cleaning surfaces with water, detergents, and disinfectants usually effective to clean the environment. In relation to this, Akram (2020) has reported that disinfection of frequent touch surfaces with 62–71% ethanol, 0.1% sodium hypochlorite, and 0.5% hydrogen peroxide is effective against SARS-CoV-2, but ineffective with 1-minute exposure time. Other biocidal agents such as 0.05-0.2% benzalkonium chloride, or 0.02% chlorhexidine digluconate, are less effective ( Kampf et al, 2020a ).…”
Section: Miscellaneous On Covid-19 and Surfaces: Mitigation Of The Comentioning
confidence: 99%
“…Goldman ( 2020 ), for instance, proposes that a risk of infection exists if a person touches a surface immediately after (1–2 h) an infected person directly coughed or sneezed on it. Other scholars suggest that the virus may survive between 2 or 3 days on dry surfaces (Van Doremalen et al, 2020 ) or even up to 9 days at room temperature (Akram, 2020 ; Fiorillo et al, 2020 ). Hence, touching surfaces while traveling carries the risk of infection with the coronavirus, with the original transmitter being unknown and hard to trace for those that are infected (Suman et al, 2020 ).…”
Section: Conceptual Research Frameworkmentioning
confidence: 99%
“…According to a Lancet report, the infectious virus was undetectable at day four on glass and a banknote, and at day seven on stainless steel and plastic [92]. SARS-CoV-2 maintains its infectivity up to 24 h, 48 h and 72 h on cardboard, stainless steel and plastics, respectively, whereas copper tends to inactivate the virus since SARS-CoV-2 was found to persist up to a maximum of 4 h only on copper surfaces [93]. In terms of disinfections, SARS-CoV-2 is susceptible to many disinfectant agents, including ethanol (62-71%), sodium hypochlorite (0.1%) and hydrogen peroxide (0.5%) [91].…”
Section: Virus Stability On Surfacesmentioning
confidence: 99%